Inflamasi dalam Patologi Penyaki Alzheimer - Jan S. Purba (PT Dexa Medica, 2020)
The worldwide incidence of Alzheimer's disease (AD) in 2006 was estimated to be 26.6 million; and is expected to quadruple by 2050 because of the increasing life expectancy in many countries. The main cause of AD is generally attributed to increased production and accumulation of β-amyloid (Aβ), in association with neurofibrillary tangles (NFT) formation and synaptic degeneration. Increased levels of proinflammatory factors such as cytokines and chemokines, and the activation of complement cascade that occurs in the brains of AD patients contributes to local inflammatory response triggered by amyloid plaque. The same type of amyloid beta proteins which is the hallmark of Alzheimer's when found in the brain are also found in the lens and ocular fluid. These proteins produce an unusual type of cataract in a different part of the eye than common cataracts. Studies showed that after the release of Aβ, synaptic activity in the neurons is increased through a positive feedback loop, and disrupting this positive feedback loop might be the key for the prevention of the earliest signs of Alzheimer's. Epidemiological findings show reduced prevalence of AD upon long-term medication with nonsteroid antiinflammatory drugs (NSAID). On the other hand, neuronal-type nicotinic acetylcholine receptors (nAChRs), peroxisomal proliferator-activated receptors (PPARs) are involved in AD-induced neuroinflammation and in this regard, future therapy may focus on their specific targeting in the AD brain.